Efforts to Improve Public Speaking Skills for New Students - Putri Naira (TRANSFORM: Journal of English Language Teaching and Learning, 2024)
This article discusses the importance of public speaking skills in various aspects of life, ranging from academic to professional settings. Public speaking not only enhances communication abilities but also builds confidence and leadership skills. Through the analysis of various techniques and strategies, the article provides insights into how to develop public speaking skills, including mastery of content, body language, and audience management. By understanding and applying public speaking skills, individuals can improve their communication effectiveness, influence others, and open new career opportunities. Research shows that students actively engaged in public speaking tend to achieve higher academic performance and are better prepared to enter the workforce. Therefore, the development of public speaking skills should be a focus in higher education curricula to produce graduates who are competent in facing global challenges.